Viral Haemorrhagic Septicemia (VHS) Disease - Bunnajirakul, Sumrarn (Journal of Mahanakorn Veterinary Medicine, 2022)
VHS disease has had devastating consequences on the production of freshwater and marine fish. Epidemiological reports reveal in North America, Asia and Europe. Outbreak strains include Genotype I, II, III and IV. Moribund fish showed retard swimming, dark skin, exopthalamos, paled gill and high mortality rate. Histopathological alterations showed focal necrosis, degeneration - cytoplasmic vacuoles, pyknosis, karyolysis and lymphocytic invasion in kidney, liver and spleen. Real-time RT-PCR for direct detection VHSV genome in tissue was recommended for confirmatory method. Pathogen monitoring, selection of fish from reliable sources and biosecurity control should be considered for surveillance program in risked cultivated fish.